Questioning Skills in the Digital Age: Teachers' Tasks and Challenges - leba, imanuel herlimus; Ekawati, Ratna; Arifin, Slamet (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research explores questioning skills in the digital age as an essential competency in modern education. These skills support students' cognitive development, strengthen teacher-student interaction and promote critical thinking. This study examines teachers' tasks and challenges in developing students' questioning skills using digital technology. The approach used is a systematic literature review that analyzes recent articles to identify effective strategies as well as barriers faced by teachers. The findings show that technology-based strategies, such as project learning and virtual simulations, improve students' questioning skills by creating an interactive learning environment. However, barriers such as the digital divide and teachers limited technological expertise hinder full implementation. This research provides recommendations for technology-integrated teacher training to enhance effective questioning skills. The implication is that collaboration between teachers and curriculum developers is necessary to optimally utilize technology opportunities and create critical and meaningful learning experiences in the digital era.